Integrated land and water planning reverses migration of tribal communities in the Ganga Basin - Singh, R.; Garg, K. K.; Anantha, K. H.; Venkataradha, A.; McCartney, Matthew P.; Arun, S.; Kumar, S.; Jat, M. L. (International Water Management Institute, 2024)
The success of a landscape rejuvenation project led by ICRISAT with support from NEXUS Gains in Poora Birdha village, India, is a shining example of how integrated approaches create sustainable, climate-resilient solutions. By implementing integrated water and natural resource management practices, local farmers have been able to rejuvenate their agricultural lands, reverse migration, and improve their livelihoods.